KORELASI USIA IBU PADA MASA KEHAMILAN DENGAN PERKEMBANGAN EMOSI ANAK USIA 3-5 TAHUN - Deni Suciati; Nurun Ayati Khasanah; Fitria Edni Wari (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Children are a valuable asset of a nation. Pre-school age is 3-5 years, most of the body’s systems are mature,stable and can adapt to environmental changes.. The prevalence of emotional and behavioral disorders in pre-school children is quite high, namely 34.10%. The main factor for children’s emotional development problem is the mother’s age during pregnancy. The type of research used observational research with analytic survey research methods. The research design used a cross-sectional study. The research subjects were all patients who came clinic. Conducted from October 2022 to December 2022 at TPMB Denny's Bojonegoro. The sample of this research 74 respondents. The analysis used is chi square and multiple logistic regression. The results of the study showed that 37 respondents (50%) were aged <20 years during pregnancy and 39 (53%) children aged 3-5 years were abnormal. Based on the results of the Chi Square test, the Asimp Sig value was 0.009. Because the value of Asimp Sig 0.009 smaller than 0.05, so it is concluded that H1 is accepted, which means “there is a significant relationship between maternal age during pregnancy and the emotional development of children aged 3-5 years